Efeito do processamento e do uso de cimentos resinosos de diferentes viscosidades no comportamento mecânico de vitrocerâmicas - May, Michele Mirian (2021)
This thesis comprises three studies that address as a central theme the effect of adhesive protocol with resin cements at different viscosities on the mechanical behavior of lithium disilicate machined ceramics. The first study aimed to access the available scientific literature on the effect that procedures performed before cementation develop on the strength of computer-aided design; computer-aided manufacturing (CAD-CAM) glass-ceramics restorations. A systematic review was conducted for in vitro studies, accessing the PubMed/MEDLINE, Web of Science, and Scopus databases. Of the 2764 potential articles found in the search, 42 were selected for full reading and 12 articles were included in the metaanalysis. It was concluded that the flexural strength of CAD-CAM glass-ceramics is reduced by grinding procedures, such as machining and fitting adjustment. Furthermore, ceramic microstructure, hydrofluoric acid concentration, and etching time determined the influence of hydrofluoric acid etching on the flexural strength and surface roughness of glass-ceramic materials. The second study analyzed whether high and low viscosity resin cement coating influenced the fatigue strength of machined vs polished lithium disilicate. Ceramic discs were obtained by machining in a CEREC inLab system and from reducing CAD-CAM blocks into cylinders, slicing in a cutting machine and polishing. Six experimental groups were evaluated, according to the surface characteristic (machined or polished), cementation protocol (coated or uncoated) and the cement used (high or low viscosity). The specimens were submitted to flexural fatigue strength test (n=15) by the "step-stress" method (10,000 cycles per step, frequency of 20 Hz, initial tension 60 MPa and increments of 20 MPa), in a piston-on-three ball test configuration, as well as roughness and contact angle analysis and scanning electron microscopy topographic and fractographic analysis. It was concluded that the cement coating was able to revert the damage effect caused by machining on the fatigue behavior of lithium disilicate. Furthermore, the behavior of high and low viscosity cements was similar regarding to ceramic strengthening. The third study evaluated the fatigue failure load of machined and polished lithium disilicate discs cemented to a dentin analogue material. The study had four experimental groups, according to the surface characteristic (machined or polished) and the cement used (high or low viscosity). The fatigue failure load and number of cycles for fatigue failure were determined using the “step-stress” method (n = 15) (10,000 cycles per step at a frequency of 20 Hz, initial load of 500 N and increments per step of 100N). Similarly to the second study, surface roughness analyzes were conducted before cementation, surface topography and fractographic analysis were done after fatigue test. The results showed that when lithium disilicate ceramic is cemented to a dentin analog support substrate, the deleterious effects of machining were not reverted by the resin cement bonding. No differences were found in the fatigue performance for the two investigated cement viscosities.